2009
DOI: 10.1097/pcc.0b013e3181a320cd
|View full text |Cite
|
Sign up to set email alerts
|

External ventricular drains in pediatric patients*

Abstract: EVDs were placed for TBI, ventriculoperitoneal shunt failure and new-onset hydrocephalus. The overall complication rate was 26%. Complication rates were similar in TBI and hydrocephalus patients, and with EVDs inserted in either the PCCU or OR. Prophylactic antibiotics or antimicrobial-impregnated catheters directed against coagulase-negative Staphylococcus may reduce EVD infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 38 publications
(62 reference statements)
0
51
0
Order By: Relevance
“…15,18) In our standardized protocol, the maximal insertion depth was 6 cm. Malplacement during the EVD procedure is a commonly described complication, 6,16) although previously published studies do not analyze the causes in full detail. In particular, notes or details on iatrogenic influence factors have been missing (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,18) In our standardized protocol, the maximal insertion depth was 6 cm. Malplacement during the EVD procedure is a commonly described complication, 6,16) although previously published studies do not analyze the causes in full detail. In particular, notes or details on iatrogenic influence factors have been missing (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…3,5,6,8,10,12,[15][16][17][18][19][20][21] In particular, EVD-associated infections were found in 0% to 20% of patients in previous studies (Table 1), and the risk of surgery-associated hemorrhages or EVD device malplacements are often described. 3,5,6,10,12,[15][16][17][18][19][20][21] The highest reported complication rate of 33% shows the possible understatement of the catheter-associated complication risk. 15) The question still remains why this variety of perioperative complications is found and whether iatrogenic factors influence the surgical complication rate and thus the outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Ngo et al [6] reported some indications based on their experience, however, this study was limited by a small sample size and a lack of etiological description (causes were simply condensed into VPS failure, new onset hydrocephalus or traumatic brain injury). Moreover, by including secondary EVD placement after VPS failure, they were unable to adequately describe the true indications for primary EVDs.…”
Section: Introductionmentioning
confidence: 99%
“…Almost all the reports are related to infections or hemorrhages, and the rate of misplacement is ranging from 12.3% to 60.1% [1]- [5]. Ngo et al reported the rate of malplacement in pediatric cases at approximately 3% [6]. Transient neurological complications are apparently very rare and to our best knowledge, there is only one case report of transient coma due to the direct compression of the brain stem by a drain [7].…”
Section: Introductionmentioning
confidence: 99%